Pulang Bale Marriage Traditions and Child Care Issues: A Study of Ḥaḍānah and Family Resilience in Aceh - Fauzi Fauzi; Lukman Hakim; Ahmad Sunawari Long; Taslim HM Yasin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Pulang bale refers to a marriage that is carried out after death of the spouse (either husband or wife) with his/her siblings. This article aims to analyze pulang bale marriages in Aceh in relation to child protection. The facts so far show that many marriage models do not support their protection. To elaborate on this, researchers will highlight how this marriage typology can ensure support for the ḥaḍānah and how this typology encourages family resilience in protecting the children. Data was obtained through in-depth interviews and observations using qualitative technical analysts. This research used a Fiqh Munākaḥah and a sociological approach. The results of the research were; first, marriage strengthens the ḥaḍānah of children due to blood relationships (musaharah) and emotional between the child’s mother and stepmother. Second, family resilience is strengthened by the same extended family and there is minimal chance of conflict both economic and social. As a finding, pulang bale with the applicable customary provisions is a marriage typology that strengthens the family's commitment and resilience